Thidiazuron affects the quality of 'Gala' apples stored under controlled atmosphere - Giehl,Ricardo Fabiano Hettwer (2010)
This work was carried out aiming to evaluate the effect of thidiazuron (TDZ) on the quality of 'Gala' apples stored under controlled atmosphere (CA) conditions. Plants were sprayed at full bloom with TDZ at 0, 10, 20, or 40g ha-1 (a.i.). Harvested fruits were then stored in CA with 1.0+2.5, 1.5+2.5 and 1.5+5.0 (kPa O2+kPa CO2), both at 0.5°C. In addition, the partial pressure of 1.5kPa of O2+2.5kPa of CO2 was also evaluated at -0.5°C. Higher flesh firmness and titratable acidity was obtained by applying 20 or 40g ha-1 TDZ. Furthermore, these TDZ doses decreased the respiration rate as well as the occurrence of flesh breakdown, mealiness and decay. The application of TDZ at doses ranging from 20 to 40g ha-1 maintains higher fruit quality for up to 8 months under CA. In addition, the storage of 'Gala' apples under CA with 1.0kPa O2+2.5kPa CO2 at 0.5°C results in higher flesh firmness and titratable acidity. Moreover, this CA condition reduces the incidence of flesh breakdown, mealiness and postharvest decay in 'Gala' apple fruits.